Index method of the acoustic quality assessment of sacral buildings - Zbigniew ENGEL; Krzysztof KOSAŁA (Archives of Acoustics)
Regardless of numerous references concerning investigations and creation of acoustic conditions in sacral buildings, there is a lack of a uniform, specific methods which allow to assess the acoustic quality of such interiors. The new index method of assessing acoustic properties of sacral buildings by means of a single number – the global index of an acoustic quality – is presented in the paper. The global index is a function of several partial indices. The method of the calculation of the global index as well as of five partial indices, namely: the reverberation index, the intelligibility of speech index, the uniformity of loudness index, the external disturbance index and the music sound quality index are given. The proposed scale of the tentative assessment of the acoustic quality of interiors of sacral building on the bases of the global index is shown. The index method was applied to four selected roman-catholic churches.